3D Surface Reconstruction of Stone Tools by Using Four-Directional Measurement Machine - Altantsetseg, Enkhbayar; Muraki, Yuta; Chiba, Fumito; Konno, Kouichi (International Journal of Virtual Reality, 2011)
In this paper, we present a whole procedure for constructing 3D models of stone tools including scanning, data acquisition and surface reconstruction with hole-filling. The process of scanning hundreds or thousands of small objects is time consuming. Our original 3D laser scanner optimizes the scanning process and reduces time significantly by four directional scanning of many small objects simultaneously. To reconstruct surface of stone tools, the scanned point clouds are processed with a new triangulation method that preserves the properties of sharp edges. Our approach is based on a projection based method in which points are distinguished into neighboring layers with a point cloud slicing method to be individually reconstructed. In addition, we introduce a simple hole-filling algorithm for mesh completion of models. The main advantages of our approach are speed and efficiency for reconstruction of many small objects.